Epidemiological, Clinical, and Laboratory Features of Children With COVID-19 in Turkey - Karbuz, Adem; Akkoc, Gulsen; Bedir Demirdag, Tugba; Yilmaz Ciftdogan, Dilek; Ozer, Arife; Cakir, Deniz; Hancerli Torun, Selda; Kepenekli, Eda; Erat, Tugba; Dalgic, Nazan; Ilbay, Sare; Karaaslan, Ayse; et al. (Frontiers in Pediatrics, 2021)
Objectives The aim of this study is to identify epidemiological, clinical and laboratory features of COVID-19 in children. Methods A retrospective study was conducted by pediatric infectious disease specialists from 32 different hospitals from all over Turkey by case records form. Pediatric cases who were diagnosed as COVID-19 between March 16 2020- June 15 2020 were included. Case characteristics including age, sex, dates of disease onset and diagnosis, family, and contact properties were recorded. Clinical data, including the duration and severity of symptoms, were also collected. Laboratory parameters like biochemical tests and complete blood count, chest X-ray, chest computed tomography (CT) were determined. Results There were 1156 confirmed pediatric COVID cases. Male cases constituted 50.4% (n=580), and females constituted 49.6% (n=571) of total. The median age of confirmed cases was 129 months (0-216). Eighty-five cases were younger than one year of age (8.1%), and 254 cases were older than 15 years of age (24.2%) among total cases. The most common symptom of patients at the first visit was; fever (52.4%) (n=583) for median 2 days (1-14 days). Fever was median 38.4 (37.5-41) °C. Second most common symptom was cough (n=543, 50.8%). The other common symptoms were; sore throat 12.7% (n=143), myalgia 12.6% (n=141), dyspnea 10.4% (n=118), diarrhea 9.9% (n=112), stomachache 6.1% (n=71) and nasal discharge 5.4% (n=63). The prevalence of asthma was 4.0% in this study group. Need for hospitalization did not differ between patients who had underlying condition and who did not (p=0.38) but need for intensive care was higher in patients who had an underlying condition (p=0.001). When patients were classified according to disease severity, 248 (21.8%) patients were asymptomatic, 667 (58.5%) patients had mild disease, 209 (18.3%) had moderate, and 16 (1.4%) cases had severe disease. Conclusions To the best of our knowledge, this is the largest pediatric data about confirmed COVID-19. Children from all ages appears to be susceptible to COVID-19, and there is significant difference by age, underlying condition or symptomatology.